El equipo interdisciplinar como instrumento básico en cuidados paliativos: a propósito de un caso - Ibáñez, Celia; Ávila, Reyes; Gómez, María Dolores; Díaz, Rafael (Psicooncología, 2008)
Describes the case of a patient diagnosed with squamous cell carcinoma of the head neck, which joins the palliative care unit of the Hospital Virgen de la Poveda for symptomatic control and family to care claudication. The patient presented at admission an acute confusional syndrome, which runs with ideas and attempts to escape, in addition to other symptoms changing. In the primary caregiver there is a grieving process advance “maladjusted” and multiple cognitive biases and misconceptions about the process of the disease. The objectives of the interdisciplinary team went to symptomatic control, improved communication, maladjusted early resolution of mourning and farewell. The patient remained joined thirty-two days at our center; this time aimed at symptomatic control was achieved in full, until death. The primary caregiver was emotionally tied to her husband. They were able to say goodbye.